1996
DOI: 10.1016/0014-5793(96)00685-0
|View full text |Cite
|
Sign up to set email alerts
|

The active sites of cellulases are involved in chiral recognition: a comparison of cellobiohydrolase 1 and endoglucanase 1

Abstract: The cellulases ceHobiohydrolase 1 (CBH 1) and endoglucanase 1 (EG 1) from the fungus Trichoderma reesei are closely related with 40% sequence identity and very similar in structure. In CBH 1 the active site is enclosed by long loops and some antiparallel ~strands forming a 40 A long tunnel, whereas in EG 1 part of those loops are missing so that the enzyme has a more common active site groove. Both enzymes were immobilized on silica and these materials were used as chiral stationary phases for chromatographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 15 publications
4
49
0
4
Order By: Relevance
“…Previous studies using LC with Cel7A as a chiral selector have shown that resolution, selectivity and retention times increase with increasing pH [1,2,6,[30][31][32][33][34][35][36] due to stronger electrostatic binding between the analyte and Cel7A. Similar pH dependence for the interaction between lipophilic amino alcohols and cellulases has been observed in CE [19].…”
Section: Phsupporting
confidence: 57%
“…Previous studies using LC with Cel7A as a chiral selector have shown that resolution, selectivity and retention times increase with increasing pH [1,2,6,[30][31][32][33][34][35][36] due to stronger electrostatic binding between the analyte and Cel7A. Similar pH dependence for the interaction between lipophilic amino alcohols and cellulases has been observed in CE [19].…”
Section: Phsupporting
confidence: 57%
“…16 If alprenolol is less hydrophobic than propranolol, why is the apparent enantioselectivity of the former always larger than that of the latter? 16,24 Our study shows that this is explained by the chiral equilibrium constant of the first enantiomer (a 1,II ) and the equilibrium constant of the nonselective interactions (a I ) being both relatively small compared to the chiral equilibrium constant of the second enantiomer (a 2,II ) in the case of alprenolol, while this is not so for propranolol. In fact, the relative values of the three constants is such that both the apparent and the true enantioselectives of alprenolol are much larger than those of propranolol, although S-propranolol has a larger enantioselective binding constant than S-alprenolol, in agreement with its higher hydrophobicity.…”
Section: Discussionmentioning
confidence: 77%
“…The active site of EG1 is a groove rather than a tunnel (Henriksson et al, 1996), allowing glucan chains to be cleaved randomly to two shorter chains resulting in a rapid decrease in DP (KlemanLeyer et al, 1992(KlemanLeyer et al, , 1994Srisodsuk et al, 1998;Whitaker, 1957;Selby, 1961;Wood and McCrae, 1978). Endoglucanase activity is most often measured based on the rate of change of the viscosity of a soluble cellulose derivative such as carboxymethylcellulose (CMC) (Miller et al, 1960;Wood and McCrae, 1972).…”
Section: Trichoderma Reesei Cellulase Systemmentioning
confidence: 99%